A dieter who cheats / Nurul Ain and Muhamad Safiq - Ain, Nurul; Safiq, Muhamad (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2021)
As soon as the word COVID-19 pandemic strikes, the common gesture enforced by the government is a lockdown. One of the infamous coping mechanisms adapted by the majority of Malaysian citizens is eating. Home confinement inflicted by the mandatory lockdown might have prompted the perpetual access of food availability which consecutively turned into overeating. 81% of participants reported by the study done by Ramalho. et al., (2021) are overeating during lockdown. The above situation warrants for effective weight loss strategies increasingly fervent, as overeating has been strongly associated with weight gain. Exercise may seem like a perfect answer; however, outdoor activity restriction imposed by the lockdown makes incorporating exercise as a solution slightly defective.